Degradation of chemical warfare agents over cotton fabric functionalized with UiO-66-NH2. Issue 72 (12th December 2018) - Kim, Min-Kun; Kim, Sung Hun; Park, Myungkyu; Ryu, Sam Gon; Jung, Hyunsook
Abstract : We develop a very efficient modification method of cotton fabric to be functionalized with a MOF via mercerization. Abstract : Herein, cotton fabric was treated with an alkaline solution to increase the content of surface hydroxyl groups and then functionalized with UiO-66-NH2, a nanoporous metal–organic framework. Instrumental analysis of the thus treated fabric revealed that its surface was covered with UiO-66-NH2 crystals in a uniform manner. The ability of the functionalized fabric to degrade two chemical warfare agents (soman and sulfur mustard) was probed by testing its permeability to these two agents (swatch testing), and the excellent degradation performance was concluded to be well suited for a broad range of filtration and decontamination applications.